Uji Aktivitas Antibakteri Dari Ekstrak Daun Sirih Terhadap Bakteri Bacillus cereus - Ali Ahmatul Umri Hasibuan; Grace Amelia Br Tarigan; Khadra Ulfah Rambe; Sisilia Anabina Tarigan; Endang Sulistyarini Gultom (Universitas Nusantara PGRI Kediri, 2024)
This study elucidates the role of secondary metabolites in green betel leaves (Piper betle) as antibacterial agents against Bacillus cereus, a bacterium causing various foodborne illnesses in humans. The experimental research was conducted at the Biology Laboratory, Faculty of Mathematics and Natural Sciences, Universitas Negeri Medan, utilizing Bacillus cereus bacterial isolates and extracting betel leaves using water. The measurement of inhibition zones was performed to evaluate the antibacterial activity of the betel leaf extract. The research results indicate the presence of an inhibition zone against Bacillus cereus growth, albeit categorized as weak. The measurements varied across repetitions, namely 2.6 mm, 3.35 mm, and 1.05 mm. The average of these three results was 3 mm.